A dynamic analysis of research and development incentive on China's photovoltaic industry based on system dynamics model. (15th October 2021) - Xin-gang, Zhao; Wei, Wang; Ling, Wu
Abstract: Government policies and investments in the photovoltaic power generation industry have contributed to the fast development of the photovoltaic power generation industry through technology push. But how does the research and development (R&D) investment affect the photovoltaic power generation industry, and what is its effect? This is a problem worthy of discussion. In order to answer this question scientifically, this paper constructs a system dynamics model to study the impact of R&D investment on China's photovoltaic power generation industry and analyzes the impact of other incentive policies such as Feed-in Tariff (FIT) on the photovoltaic industry. The results show that: firstly, R&D investment and FIT are conducive to the technological innovation of China's photovoltaic power generation industry. Secondly, a higher level of R&D investment can induce more cost reduction of photovoltaic power industry. Finally, the effect of FIT in promoting the growth of installed capacity of the photovoltaic power generation industry is more obvious. Highlights: The relationship between PV industry and technology innovation is reviewed. R&D investment and FIT are conducive to the technology innovation of PV industry. A higher level of R&D investment can induce more cost reduction of PV industry. FIT policy is more effective for the expansion of PV installed capacity.